Competition, Imitation, and Technical Change : Quality vs. Variety - Cusolito, Ana (2012)
Some researchers have documented that the path of development is remarkably related to the pattern of sectoral diversification. Others have highlighted the relation between productive specialization and economic progress. This paper explores the role of product market competition and intellectual property rights protection in the pattern of sectoral diversification. The paper confirms the insight of the innovation literature, that competition induces firms to specialize and upgrade the quality of existing goods. However, it reveals a new force, called the imitation effect, through which competition biases technical change toward product diversification. The paper shows that if knowledge spillovers increase with imitation, or the degree of product substitution is high, weak protection of property rights encourages firms to create low-quality goods, thereby directing technical change toward diversification. The predictions are tested with data on Italian firms' innovation activity. They are found to be consistent with observed behavior.